High-speed intelligent power converter IC - Putra, Nicholas Kenneth Naga (Nanyang Technological University, 2022)
Switched-mode DC-DC converter (power converter) is an important electronic circuit to perform the voltage conversion in electronic devices. Switched-mode DC-DC converter architectures generally have a feedback loop for output regulation. An important part of the loop is the output inductor of the converter as its value may determine the loop stability. The value of the inductor, however, has to be chosen conservatively as it generally determines the size of the converter. Fully-integrated converters, where the inductor is integrated either on the IC or within the IC package, are increasingly popular for miniature and portable applications. To shrink the inductor size, the converter typically operates at high switching-frequencies (> 50 MHz).